Lightweight aggregate as well as preparation method and application thereof

By converting steel slag and waste ceramics into light aggregates and combining them with phosphate cement, a high-strength, lightweight, and environmentally friendly MPC-UHPC material was prepared, which solved the high concrete density and solid waste in the prior art. The problem of utilization has achieved resource utilization and efficient construction.

CN119430862AActive Publication Date: 2025-02-14THE THIRD CONSTR OF CHINA CONSTR EIGHTH ENG BUREAU
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411559528.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing ultra-high performance concrete is high in density, high construction weight, and fails to effectively utilize industrial solid waste, resulting in waste of resources and environmental pollution.

Method used

Lightweight aggregate made of steel slag and waste ceramics, combined with phosphate cement, is prepared to prepare lightweight MPC-UHPC materials. The aggregate consists of steel slag, waste ceramics and active blends, and is prepared through steps such as crushing, stirring, granulation, sintering and surface treatment.

Benefits of technology

It realizes the multiple needs of resource utilization, environmental protection, lightweight and high performance, and provides an MPC-UHPC material with high strength, durability and lightweight characteristics, suitable for a variety of engineering application fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides lightweight aggregate as well as a preparation method and application thereof, and relates to the technical field of aggregate, the lightweight aggregate comprises steel slag, waste ceramic and an active admixture. According to the invention, the steel slag and the waste ceramic are converted into the lightweight aggregate, and the lightweight aggregate is combined with the phosphate cement, so that the MPC-UHPC material with high strength, durability and lightweight characteristics is provided, and the material has excellent corrosion resistance, lightweight property and high early strength, and has significant advantages in the aspects of environmental protection and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aggregates, in particular to a lightweight aggregate and a preparation method and application thereof. Background Art

[0002] Traditional ultra-high performance concrete (UHPC) mostly uses high-density, high-strength aggregates. Although it has excellent mechanical properties, it has a high density and heavy construction weight, which imposes an additional burden on the engineering structure. At the same time, a large amount of construction and industrial solid waste (such as steel slag and waste ceramics) has not been effectively utilized, resulting in resource waste and environmental pollution. The existing technology still lacks an MPC-UHPC material that can combine lightweight, environmental protection and high strength characteristics.

[0003] Phosphate cement (MPC) is a cement-based material with high early strength, rapid curing and chemical corrosion resistance. The preparation of MPC-UHPC and its prefabricated components by synergizing MPC cement with solid waste-based lightweight high-strength aggregate can, on the one hand, make high-value resource utilization of industrial solid waste, and on the other hand, it has the characteristics of ultra-early strength, and does not require additional special maintenance measures such as high-temperature steam curing, which is extremely efficient and energy-saving. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention proposes a lightweight aggregate made of steel slag and waste ceramics, combined with phosphate cement to prepare lightweight MPC-UHPC, which can achieve multiple requirements of resource utilization, environmental protection, light weight and high performance.

[0005] The invention provides a lightweight aggregate comprising steel slag, waste ceramics and active admixture.

[0006] Preferably, by mass percentage, the steel slag is 60%-70%, the waste ceramics is 20%-30%, and the active admixture is 5%-10%.

[0007] The present invention also provides a method for preparing the lightweight aggregate, comprising the following steps: Step 1: crush the steel slag and waste ceramics to a particle size of less than 2mm, sieve to remove fine particles, remove oxides in the steel slag and dust on the surface of the waste ceramics, wash with water and dry at 80°C for 1-2h to reduce moisture content and prevent adverse reactions in subsequent processes; the steel slag and waste ceramics should be selected uniformly without harmful impurities. Steel slag contains mineral components such as calcium, silicon, and iron, and waste ceramics have good pore structure and high durability; Step 2: In a mixer, steel slag, waste ceramic powder and active admixture are mixed in a certain proportion, and appropriate amount of water is added to make the humidity of the mixture reach 10%-12%, to ensure uniform granulation and avoid over-drying or over-wetting; the active admixture can be silica fume and nano-silicon oxide, silica fume can improve the interface performance of aggregate, and nano-silicon oxide can enhance the overall strength and density; Step 3: The mixture is granulated by a rotary disc granulator or a roller granulator. The aggregate particle size after granulation is 0.5-4 mm, which is suitable for lightweight UHPC. The granulation time is 10-15 minutes to ensure uniform particles. After granulation, the aggregate is dried at 80°C for 2-3 hours to remove excess moisture to avoid excessive expansion of the pore structure during sintering; Step 4: The dried aggregate is fed into a high-temperature kiln, and the temperature is gradually raised to 1000-1200°C at a heating rate of 10-15°C / min. The aggregate is sintered at 1000-1200°C for 20-30 minutes. A temperature higher than 1000°C can promote the full reaction of the components of the steel slag and the waste ceramics to form a dense surface structure. After sintering, the aggregate is cooled to room temperature, usually by air cooling or water spray cooling, so as to stabilize the pore structure and microstructure. The high-temperature sintering treatment forms a porous structure inside the aggregate, which can reduce the aggregate density and ensure high strength. Step 5: Immerse the sintered aggregate in a 1%-2% silane coupling agent solution for 5-10 minutes. This process helps to improve the bonding strength between the aggregate and the cement matrix and reduce water absorption. After silane coupling agent treatment, further spray nano-silicon oxide or nano-aluminum oxide solution (0.5%-1% concentration) to form a thin layer coating to enhance the durability of the aggregate. The coated aggregate is dried at 80°C for 1-2 hours to ensure that the coupling agent and nano-coating are completely cured to improve the surface performance of the aggregate.

[0008] The lightweight aggregate prepared from steel slag and waste ceramics has a density of 500-900 kg / m³ and a compressive strength of 15-30 MPa.

[0009] The present invention also provides the use of the lightweight aggregate or the lightweight aggregate prepared by the preparation method in the preparation of phosphate cement ultra-high performance concrete.

[0010] Preferably, the method for preparing the phosphate cement ultra-high performance concrete comprises the following steps: Step 1: Add phosphate cement dry powder and lightweight aggregate into a forced mixer in proportion, and stir at a rate of 90-120 rpm for 1-2 minutes to make the phosphate cement dry powder and lightweight aggregate evenly mixed; Step 2: Continue stirring at a rate of 90-120 rpm for 2-3 minutes, and gradually add water during the stirring process to ensure that the cement and aggregate are evenly distributed, and the aggregate and cement paste are evenly wrapped; Step 3: Adjust the stirring rate to 250-300 rpm and continue stirring for 1-2 minutes to form a uniform slurry; Step 4: Pour the evenly mixed slurry into the mold and gently vibrate the mold to expel bubbles and ensure the density of the material; Step 5: After pouring, cover the surface and let it stand at room temperature (20-25℃) for 1-2 hours to wait for the phosphate cement to initially set, then remove the formwork and transfer it to the curing room for curing for 28 days.

[0011] Preferably, the mass percentage of the lightweight aggregate is 30%-50%, and the mass ratio of the phosphate cement dry powder to water is 1:0.2-0.25.

[0012] Preferably, the preparation method of the phosphate cement dry powder comprises the following steps: mixing magnesium oxide powder, phosphate, boric acid (B2O3) or borax (Na2B4O7) under dry conditions, stirring at a low speed using a variable speed mixer, stirring at a rate of 90-120 rpm for 5-10 minutes to avoid particle agglomeration and ensure uniform mixing. Adding boric acid (B2O3) or borax (Na2B4O7) can adjust the reaction rate and the exothermic characteristics during the hydration process.

[0013] The magnesium oxide powder is selected from high purity (purity ≥ 95%) magnesium oxide powder with moderate calcination temperature. The reactivity of magnesium oxide depends on its calcination temperature. The present invention selects light magnesium oxide powder with a calcination temperature of 700-900°C, which has high chemical reactivity.

[0014] The phosphate is selected from potassium dihydrogen phosphate (KH2PO4) or ammonium dihydrogen phosphate (NH4H2PO4), which can react rapidly with magnesium oxide to form magnesium phosphate hydrate.

[0015] Preferably, the mass ratio of magnesium oxide to phosphate is 1.5-2:1, which can ensure sufficient reaction and avoid excessively rapid generation of magnesium phosphate.

[0016] Preferably, the amount of boric acid or borax added is 0.5%-2% by weight of the phosphate to adjust the setting time.

[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention converts steel slag and waste ceramics into lightweight aggregates and combines them with phosphate cement to provide an MPC-UHPC material with high strength, durability and light weight. The material has excellent corrosion resistance, light weight and high early strength, and can be used in engineering applications such as bridge structures, marine engineering, underground structures, high-rise buildings, etc. that require light weight, high strength, high durability and corrosion resistance.

[0018] 2. Green environmental protection and resource utilization: The present invention utilizes steel slag and waste ceramics to produce lightweight aggregate, thus achieving efficient utilization of solid waste resources and having both environmental and economic benefits.

[0019] 3. Lightweight and high strength: The present invention adopts lightweight aggregate and MPC matrix material, which significantly reduces the weight of MPC-UHPC material while ensuring high strength, thus expanding its application scenarios.

[0020] 4. Rapid solidification and convenient construction: The rapid solidification of the MPC of the present invention makes the lightweight MPC-UHPC material suitable for rapid construction, shortens the construction period, and improves the construction efficiency. DETAILED DESCRIPTION

[0021] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0022] Embodiment 1: A method for preparing phosphate cement ultra-high performance concrete, comprising the following steps: Step 1: Add phosphate cement dry powder and lightweight aggregate into a forced mixer in proportion, and stir at a rate of 100 rpm for 1.5 minutes to make the phosphate cement dry powder and lightweight aggregate evenly mixed; Step 2: Continue stirring at a rate of 100 rpm for 2.5 min, and gradually add water during the stirring process to ensure that the cement and aggregate are evenly distributed, and the aggregate and cement paste are evenly wrapped; Step 3: Adjust the stirring rate to 270 rpm and continue stirring for 1.5 min to form a uniform slurry; Step 4: Pour the evenly mixed slurry into the mold and gently vibrate the mold to expel bubbles and ensure the density of the material; Step 5: After pouring, cover the mold and let it stand at room temperature for 1.5 hours to wait for the phosphate cement to set initially, then remove the mold and transfer it to the curing room for curing for 28 days.

[0023] Among them, the mass percentage of the lightweight aggregate is 40%, and the mass ratio of the phosphate cement dry powder to water is 1:0.23.

[0024] Furthermore, the method for preparing the lightweight aggregate comprises the following steps: Step 1: crush the steel slag and waste ceramics to a particle size of less than 2 mm, sieve to remove oxides in the steel slag and dust on the surface of the waste ceramics, wash with water and dry at 80°C for 1.5h; Step 2: Mix steel slag, waste ceramic powder and active admixture in a certain proportion in a mixer, and add appropriate amount of water to make the humidity of the mixture reach 11%; Step 3: The mixture is granulated by a rotary disk granulator or a double roller granulator. The aggregate particle size after granulation is 3 mm. The granulation time is 12 min. After the granulation is completed, the aggregate is dried at 80° C. for 2.5 h to remove excess moisture. Step 4: The dried aggregate is fed into a high-temperature kiln, and the temperature is gradually raised to 1100°C at a heating rate of 12°C / min, and sintered at 1100°C for 25 minutes. After sintering, the aggregate is cooled to room temperature by air cooling; Step 5: Immerse the sintered aggregate in a 1.5% silane coupling agent solution for 8 minutes. After the silane coupling agent treatment, further spray nano-silicon oxide or nano-aluminum oxide solution (0.7% concentration) to form a thin layer coating. The coated aggregate is dried at 80°C for 1.5 hours.

[0025] Among them, by mass percentage, the steel slag accounts for 65%, the waste ceramics accounts for 25%, and the active admixture accounts for 10%.

[0026] Furthermore, the preparation method of the phosphate cement dry powder comprises the following steps: mixing magnesium oxide powder, phosphate and boric acid under dry conditions, stirring at a low speed using a variable speed mixer, and stirring at a rate of 100 rpm for 7 minutes.

[0027] The mass ratio of the magnesium oxide powder to the phosphate is 1.8: 1. The amount of boric acid added is 1% of the weight of the phosphate.

[0028] According to the performance test, the compressive strength of the phosphate cement ultra-high performance concrete prepared in this embodiment is 120 MPa (28 days curing age), and the dry density is 1900 kg / m³.

[0029] Embodiment 2: A method for preparing phosphate cement ultra-high performance concrete, comprising the following steps: Step 1: Add phosphate cement dry powder and lightweight aggregate into a forced mixer in proportion, and stir at a rate of 90 rpm for 2 minutes to make the phosphate cement dry powder and lightweight aggregate evenly mixed; Step 2: Continue stirring at 90 rpm for 3 minutes, and gradually add water during the stirring process to ensure that the cement and aggregate are evenly distributed, and the aggregate and cement paste are evenly wrapped; Step 3: Adjust the stirring rate to 250 rpm and continue stirring for 2 minutes to form a uniform slurry; Step 4: Pour the evenly mixed slurry into the mold and gently vibrate the mold to expel bubbles and ensure the density of the material; Step 5: After pouring, cover the mold and let it stand at room temperature for 1 hour to wait for the phosphate cement to initially set, then remove the mold and transfer it to the curing room for curing for 28 days.

[0030] Among them, the mass percentage of the lightweight aggregate is 50%, and the mass ratio of the phosphate cement dry powder to water is 1:0.2.

[0031] Furthermore, the method for preparing the lightweight aggregate comprises the following steps: Step 1: crush the steel slag and waste ceramics to a particle size of less than 2 mm, sieve to remove oxides in the steel slag and dust on the surface of the waste ceramics, wash with water and dry at 80°C for 2 hours; Step 2: Mix steel slag, waste ceramic powder and active admixture in a certain proportion in a mixer, and add appropriate amount of water to make the humidity of the mixture reach 10%; Step 3: granulating the mixture using a rotary disk granulator or a double roller granulator, the aggregate particle size after granulation is 4 mm, the granulation time is 10 min, and after granulation, the aggregate is dried at 80° C. for 3 h to remove excess moisture; Step 4: The dried aggregate is fed into a high-temperature kiln, and the temperature is gradually raised to 1200°C at a heating rate of 10°C / min, and sintered at 1200°C for 20 minutes. After sintering, the aggregate is cooled to room temperature by water spraying; Step 5: Immerse the sintered aggregate in a 2% silane coupling agent solution for 5 minutes. After the silane coupling agent treatment, further spray nano-silicon oxide or nano-aluminum oxide solution (1% concentration) to form a thin layer coating. The coated aggregate is dried at 80°C for 1 hour.

[0032] Among them, by mass percentage, the steel slag accounts for 70%, the waste ceramics accounts for 25%, and the active admixture accounts for 5%.

[0033] Furthermore, the preparation method of the phosphate cement dry powder comprises the following steps: mixing magnesium oxide powder, phosphate and borax under dry conditions, stirring at a low speed using a variable speed mixer, and stirring at a rate of 120 rpm for 5 minutes.

[0034] The mass ratio of the magnesium oxide powder to the phosphate is 2: 1. The amount of borax added is 0.5% of the weight of the phosphate.

[0035] According to the performance test, the compressive strength of the phosphate cement ultra-high performance concrete prepared in this embodiment is 100 MPa (28 days curing age), and the dry density is 1800 kg / m³.

[0036] Embodiment 3: A method for preparing phosphate cement ultra-high performance concrete, comprising the following steps: Step 1: Add phosphate cement dry powder and lightweight aggregate into a forced mixer in proportion, and stir at a rate of 120 rpm for 1 min to make the phosphate cement dry powder and lightweight aggregate evenly mixed; Step 2: Continue stirring at 120 rpm for 2 minutes, and gradually add water during the stirring process to ensure that the cement and aggregate are evenly distributed, and the aggregate and cement paste are evenly wrapped; Step 3: Adjust the stirring rate to 300 rpm and continue stirring for 1 min to form a uniform slurry; Step 4: Pour the evenly mixed slurry into the mold and gently vibrate the mold to expel bubbles and ensure the density of the material; Step 5: After pouring, cover the mold and let it stand at room temperature for 2 hours to wait for the phosphate cement to initially set, then remove the mold and transfer it to the curing room for curing for 28 days.

[0037] Among them, the mass percentage of the lightweight aggregate is 30%, and the mass ratio of the phosphate cement dry powder to water is 1:0.25.

[0038] Furthermore, the method for preparing the lightweight aggregate comprises the following steps: Step 1: crush the steel slag and waste ceramics to a particle size of less than 2 mm, sieve to remove oxides in the steel slag and dust on the surface of the waste ceramics, wash with water and dry at 80°C for 1 hour; Step 2: Mix steel slag, waste ceramic powder and active admixture in a certain proportion in a mixer, and add appropriate amount of water to make the humidity of the mixture reach 12%; Step 3: Granulate the mixture using a rotary disk granulator or a double roller granulator, the aggregate particle size after granulation is 0.5 mm, the granulation time is 15 minutes, and after the granulation is completed, the aggregate is dried at 80° C. for 2 hours to remove excess moisture; Step 4: The dried aggregate is fed into a high-temperature kiln, and the temperature is gradually raised to 1000°C at a heating rate of 15°C / min, and sintered at 1000°C for 30 minutes. After sintering, the aggregate is cooled to room temperature by air cooling; Step 5: Immerse the sintered aggregate in a 1% silane coupling agent solution for 10 minutes. After the silane coupling agent treatment, further spray nano-silicon oxide or nano-aluminum oxide solution (0.5% concentration) to form a thin layer coating. The coated aggregate is dried at 80°C for 2 hours.

[0039] Wherein, by mass percentage, the steel slag accounts for 60%, the waste ceramics accounts for 30%, and the active admixture accounts for 10%.

[0040] Furthermore, the preparation method of the phosphate cement dry powder comprises the following steps: mixing magnesium oxide powder, phosphate and boric acid under dry conditions, stirring at a low speed using a variable speed mixer, and stirring at a rate of 90 rpm for 10 minutes.

[0041] The mass ratio of the magnesium oxide powder to the phosphate is 1.5: 1. The amount of boric acid added is 2% of the weight of the phosphate.

[0042] According to the performance test, the compressive strength of the phosphate cement ultra-high performance concrete prepared in this embodiment is 110 MPa (28 days curing age), and the dry density is 1850 kg / m³.

[0043] The above are only implementation modes of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent schemes made using the contents of the present invention specification, directly or indirectly applied in other related technical fields, are also within the patent protection scope of the present invention.

Claims

1. A lightweight aggregate, characterized in that: Including steel slag, waste ceramics and active admixtures.

2. The lightweight aggregate according to claim 1, characterized in that: In terms of mass percentage, the steel slag accounts for 60%-70%, the waste ceramics accounts for 20%-30%, and the active admixture accounts for 5%-10%.

3. The method for preparing lightweight aggregate according to claim 1 or 2, characterized in that: The steps include: Step 1: crush the steel slag and waste ceramics to a particle size of less than 2 mm, sieve to remove oxides in the steel slag and dust on the surface of the waste ceramics, wash with water and dry at 80°C for 1-2 hours; Step 2: Mix the steel slag, waste ceramic powder and active admixture in a certain proportion, and add appropriate amount of water to make the humidity of the mixture reach 10%-12%; Step 3: Granulate the mixture, the aggregate particle size after granulation is 0.5-4 mm, the granulation time is 10-15 min, after granulation, dry the aggregate at 80° C. for 2-3 h to remove excess moisture; Step 4: Feed the dried aggregate into a high-temperature kiln, gradually heat it to 1000-1200°C at a heating rate of 10-15°C / min, sinter it at 1000-1200°C for 20-30 minutes, and cool it to room temperature after sintering. Step 5: Immerse the sintered aggregate in a 1%-2% silane coupling agent solution for 5-10 minutes. After the silane coupling agent treatment, further spray nano silicon oxide or nano aluminum oxide solution to form a thin layer coating. The coated aggregate is dried at 80°C for 1-2 hours.

4. Use of the lightweight aggregate according to claim 1 or 2 or the lightweight aggregate prepared by the preparation method according to claim 3 in the preparation of phosphate cement ultra-high performance concrete.

5. The use according to claim 4, characterized in that The preparation method of the phosphate cement ultra-high performance concrete comprises the following steps: Step 1: Stirring the phosphate cement dry powder and the lightweight aggregate in proportion at a rate of 90-120 rpm for 1-2 minutes, so that the phosphate cement dry powder and the lightweight aggregate are evenly mixed; Step 2: Continue stirring at a rate of 90-120 rpm for 2-3 minutes, and gradually add water during the stirring process to ensure that the cement and aggregate are evenly distributed, and the aggregate and cement paste are evenly wrapped; Step 3: Adjust the stirring rate to 250-300 rpm and continue stirring for 1-2 minutes to form a uniform slurry; Step 4: Pour the mixed slurry into the mold and gently vibrate the mold to expel bubbles; Step 5: After pouring, cover the mold and let it stand at room temperature for 1-2 hours to wait for the phosphate cement to set initially, then remove the mold and transfer it to the curing room for curing for 28 days.

6. The use according to claim 5, characterized in that The mass percentage of the lightweight aggregate is 30%-50%, and the mass ratio of the phosphate cement dry powder to water is 1:0.2-0.

25.

7. The use according to claim 5, characterized in that The preparation method of the phosphate cement dry powder comprises the following steps: mixing magnesium oxide powder, phosphate, boric acid or borax under dry conditions, and stirring at a speed of 90-120 rpm for 5-10 minutes.

8. The use according to claim 7, characterized in that The mass ratio of the magnesium oxide powder to the phosphate is 1.5-2:

1.

9. The use according to claim 7, characterized in that The added amount of the boric acid or borax is 0.5%-2% of the weight of the phosphate.

Citation Information

Patent Citations

  • Coated light-weight aggregate, and preparation method and application thereof

    CN104556767A

  • Lightweight sintering-free aggregate prepared from solid waste and preparation method of lightweight sintering-free aggregate

    CN117682782A

  • High-strength low-heat mass concrete prepared by synergistic slow release of silicon-calcium slag and porous solid waste aggregate and preparation method of high-strength low-heat mass concrete

    CN118026617A

  • PATTERN FORMING APPARATUS OF environment social governance TexTILE

    KR102646899B1